Mystic lands. Bali & Australia [videorecording (DVD)]. - Olmos, Edward James; Duncan, Chip (Mystic lands (Television program), 2006)
The Balinese Huindu faith express their devotion through music, dance and processions of beauty, but they do not take their faith lightly.